User insights as a key factor for the development of a strategic plan at the Central Library of NTUA - Kouri, Stavroula; Sisamaki, Eugenia (Qualitative and Quantitative Methods in Libraries; Vol 7 No 3 (2018): September 2018 Issue, 2019)
Strategic planning in libraries is not a common and well established activity. Probably this is because, as Nawe states, “Libraries tended to take for granted that their importance would continue to be acknowledged without any questioning” (2003, p.418). Nevertheless, libraries no longer occupy the secure position which they did in the past. Therefore, it is crucial they can enhance their importance and contribution to institutional aims and outcomes. A path towards improvement includes upgrade in managerial and service effectiveness, identification of new perspectives and insights and improvement of user satisfaction. Given the potential benefits, all libraries should focus on developing a strategic plan. According to Jacobsen and Sparks (cited in McNicol, 2005:498) “In strategy, we are trying to convert information to knowledge to a decision about a course of action in the future”. The wise use of data and information while developing a strategic plan can enhance its effectiveness in library performance (Hiller and Self, 2004). There is no point in designing services without user input. User-based determination of user needs should be considered as part of the strategic planning process (McClure, 1994). Inviting and enabling user input offers a fruitful planning approach in which libraries can design their future profile (Somerville and Collins, 2008). Even though libraries have been collecting data for a while, only recently they have started using it in library management. The issue at hand is how to properly use this data in order to improve library management and decision-making (Hiller and Self, 2004). The NTUA Central Library in order to form, execute and evaluate a strategic plan aiming to evolve its services and performance, made use of numerous of the services that HEALlink provides openly and freely to all its members. The main service that was exploited in order to collect information which led to the strategy formed was MODIPAV. MODIPAV is a service that offers electronic collection, processing, analysis and presentation of data concerning Greek Academic Libraries. The NTUA Central Library, thoroughly reviewed and interpreted user and staff insights which constituted the foundations upon the strategic plan were developed. Additional services and tools such as ILSas, AMElib CRIS and DSpace which were developed by HEALlink were also exploited and provided an advantage to the future goals of the NTUA Central Library. The goal of this attempt is to make the most of what has already been developed and is freely offered in order to continue and improve throughout this time of financial difficulties.